(untitled) (Revista de Cultura e Extensão USP, 2014)
Usually, research institutes presented a distant relationship with the laic Society. This fact results in an undervaluation of activities of social promotion or communication. In the Instituto de Medicina Tropical de São Paulo, since our foundation there were several actions for social promotion and communication, due to our research type or open field projects, but with challenging and difficult maintenance with frequent interruptions, as a research institute. Here, we present the new initiatives to enhance the interface between Society and IMTSP and we detect that the awareness of scientific staff and the “aggiornamento” of concepts and interactions were extremely beneficial to research institutes. Contradicting the initial thinking of a limited unidirectional knowledge transmission of those contacts and a “downstairs” social promotion or communication, those initiatives were more important to the scientific staff by showing the Society commitments with the support of the research, ratifying the value of the evolving research in those institutes.